Silver Nanoparticle-Doped Titanium Oxide Thin Films for Intermediate Layers in Organic Tandem Solar Cell - Wanyi Nie; Robert C. Coffin; David L. Carroll (International Journal of Photoenergy)
In this work we investigate the Ag nanoparticle doping of TiOx used as an intermediate layer between subcells of a tandem organic photovoltaic. We use a model polymer cell structure of P3HT:TiOx:PEDOT:P3HT to observe charge-trapping effects as a function of nanoparticle content in the TiOx, as determined by the shape of the dark and illuminated current voltage curves of the devices. There is a direct correlation between the amount of Ag nanoparticles in the TiOx, and interfacial charge buildup, and charge trapping being completely mitigated at around 0.2% mol. This suggests that such doping schemes might provide a simple approach to the creation and use of TiOx layers for tandem cells.